A Comparison Analysis of Monetary Policy Effect Under an Open Economy Model - Keun Yeong Lee (East Asian Economic Review (EAER), 2018)
The paper analyzes and compares the effects of domestic monetary policy using DSGE, DSGE-VAR, and VAR based on a two-country open economy model of Korea and the U.S. According to impulse response analysis, a domestic interest rate hike raises won value in the case of DSGE and DSGE-VAR models, while in the case of the unrestricted VAR model, it lowers won value. In the marginal data density standard, DSGE-VAR (μ=1) is superior to DSGE or Bayesian VAR over the sample period. Conversely, in the in-sample RMSE criterion, especially for the won/dollar exchange rate, VARs are superior to DSGE or DSGE-VAR. It is necessary to study further if these differences are caused by model misspecification or omitted variable bias.
Keywords: E10; E50; F30; F40; 330; DSGE; DSGE-VAR; Bayesian VAR; Marginal Data Density; RMSE